(3GdJSgjd hGdJbQjH aj HjGf GdMd hGdJQcjHs - (3GHf GdeLOj , TgGH GdOjf CHh GdYHGS Hf GdeLOj,J (B850 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg aUd ai Jbhje GdchGcH GdSHYI HWQjb GdCUd hcjajI MdgG hJQcjH LOGhdgG hGdYed HgG s
(3BNQgG (B:s
(3hHbi GdcdGe Ydi YWGQO abW hgh ebjS Ydi ZjQg ef GdchGcH bhHdJ Ydi NW eUfagG QMeg Gddg LgO GdWGbI s
(3gh CUd cJGH Sdc GdOQjf ai Md GdfjQjf (B" (3Qbe (B126" (3adc (B"s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B125 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B221s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B128 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B20 s
Keywords: (3Gdadcs